Cohesin Causes Replicative DNA Damage by Trapping DNA Topological Stress - Minchell, Nicola Elizabeth; Keszthelyi, Andrea; Baxter, Jonathan (Molecular cell, 2020)
DNA topological stress inhibits DNA replication fork (RF) progression and contributes to DNA replication stress. In Saccharomyces cerevisiae, we demonstrate that centromeric DNA and the rDNA array are especially vulnerable to DNA topological stress during replication. The activity of the SMC complexes cohesin and condensin are linked to both the generation and repair of DNA topological-stress-linked damage in these regions. At cohesin-enriched centromeres, cohesin activity causes the accumulation of DNA damage, RF rotation, and pre-catenation, confirming that cohesin-dependent DNA topological stress impacts on normal replication progression. In contrast, at the rDNA, cohesin and condensin activity inhibit the repair of damage caused by DNA topological stress. We propose that, as well as generally acting to ensure faithful genetic inheritance, SMCs can disrupt genome stability by trapping DNA topological stress.